Cost reduction by value stream mapping using Lean-Kaizen concept: a case study. (2018) - Kumar, Sunil; Dhingra, Ashwani Kumar; Singh, Bhim
Small and medium scale enterprises (SMEs) are under consistent pressure for improving the product quality in order to meet the customer requirements. The present case demonstrates the application of Lean-Kaizen concept using value stream mapping (VSM) for eliminating waste. Based on data collected from Shaft Swing Arm, current and future state maps have been constructed. The high rejection rate and increased lubrication oil consumption are identified as waste. Two Kaizen events; first, the high rejection rate is fixed by modifying the existing process route and second, the high consumption of lubrication oil is controlled by installing the new pipeline in the machine, have been proposed as solutions. A significant cost reduction of 7.50 lacs INR per year is recorded. Lean-Kaizen using VSM is found an effective technique to reduce the cost. The methodology will be beneficial for the managers and researchers to tackle various inefficiencies in the SMEs.